Psychometric Properties of Persian Version of the Multifactor Leadership Questionnaire - Mahdi Bagheri (Babol University of Medical Sciences, 2015)
BACKGROUND AND OBJECTIVE: Outstanding leadership has invariably emerged as a key characteristic of outstanding schools. There can no longer be doubt that those seeking quality in education must ensure its presence and that the development of potential leaders should be given high priority. Thus, effective educational leadership and adopting an appropriate tool to assess leadership in education are crucial in these institutions. The present study was conducted to develop an instrument for measuring the leadership style in faculty members. METHODS: In a descriptive cross-sectional study, Multifactor Leadership Questionnaire (MLQ) was examined using the opinions of 10 experienced faculty members as a panel of experts in order to examine the content and face validity of the scale. Moreover, a number of 210 questionnaires were administered to the faculty with Tehran University of Medical Sciences in order to examine the construct validity of the scale. Confirmatory factor analysis was run using principal component analysis and Varimax rotation method. The reliability of the scale was measured through internal consistency using Cronbach’s alpha formula. Confirmatory factor analysis was used to examine the construct validity of the questionnaire. Data analysis was conducted using SPSS16 and LISREL software. FINDINGS: The results of factor analysis and expert opinion helped develop a questionnaire with 18 items across six subscales including idealized influence, inspirational motivation, intellectual stimulation, individualized consideration, contingent reward, and management by exception. The reliability coefficient of the questionnaire was acceptable (0.90). Confirmatory factor analysis showed that the scale had appropriate goodness of fit. CONCLUSION: The 18-item Educational Leadership Questionnaire was found to have acceptable validity and reliability for measuring leadership style in the faculty. It is recommended that the questionnaire be administered to larger samples.